On the Relativistic Quantum Mechanics of a Particle in Space with Minimal Length - Scherbakov, Ch.M. (Ukrainian Journal of Physics, 2012)
A noncommutative space and the deformed Heisenberg algebra [X,P] = iħ1 – βP21/2 are investigated. The quantum mechanical structures underlying this commutation relation are studied. The rotational group symmetry is discussed in detail.